Challenges before Tea Industry of India: Analyzing the Challenges and Solutions in India's Tea Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The tea industry of India is facing difficult times. A slow growing domestic demand coupled with near stagnant external earnings has pushed the industry in a defensive state. Indian tea is facing issues related to quality of product while suffering from worker disenchantment due to low earnings simultaneously with increasing competition from other countries eager to foray into the international tea market. This paper highlights the present position of the industry while discussing the problems faced by producers and growers. An attempt has been made to suggest remedies for overcoming these problems.